Factors associated with older persons’ physical health in rural Uganda - Maniragaba, Fred; Nzabona, Abel; Asiimwe, John Bosco; Bizimungu, Emmanuel; Mushomi, John; Ntozi, James; Kwagala, Betty (Public Library of Science, 2019)
The proportion of older persons in developing countries is increasing with no clear evidence of improvement in physical health. The aim of this paper was to examine the factors associated with older persons’ physical health in rural Uganda. This paper is based on a cross-sectional study of 912 older persons age 60 years and older across four major regions of Uganda. The study was conceptualized basing on World Health Organization quality of life BREF (WHOQOL-BREF). Analysis was done at three levels, that is, frequency distributions were generated to describe background characteristics of respondents and cross-tabulations were done to determine associations between dependent and each of the independent variables. Ordinal logistic regression was used to determine the predictors of physical health.